Synthesis, structural characterisation and proton conduction of two new hydrated phases of barium ferrite BaFeO2.5−x(OH)2x. Issue 9 (8th February 2016) - Knöchel, Patrick L.; Keenan, Philip J.; Loho, Christoph; Reitz, Christian; Witte, Ralf; Knight, Kevin S.; Wright, Adrian J.; Hahn, Horst; Slater, Peter R.; Clemens, Oliver
Abstract : Materials exhibiting mixed electronic and proton conductivity are of great interest for applications ranging from electrodes for proton conducting ceramic fuel cells to hydrogen separation membranes. Abstract : Materials exhibiting mixed electronic and proton conductivity are of great interest for applications ranging from electrodes for proton conducting ceramic fuel cells to hydrogen separation membranes. In this work, we report a detailed investigation of the effect of water incorporation in BaFeO2.5 on the structure and conductivity. BaFeO2.5 is shown to be topochemically transformed to two different hydrated modifications, low-water (LW-) and high-water (HW-) BaFeO2.5 . A combined analysis of neutron and X-ray diffraction data was used to determine the crystal structure of LW-BaFeO2.5 (BaFeO2.33 (OH)0.33 ), which shows a unique ordering pattern of anion vacancies for perovskite type compounds, with structural relaxations around vacancies being similar to the chemically similar compound BaFeO2.33 F0.33 . Approximate proton positions were determined using the bond valence method. Conductivity studies of hydrated and pure BaFeO2.5 (with additional comparison to oxidized BaFeO2.5 ) show a significant enhancement of the conductivity on water incorporation, which can be attributed to proton conductivity. This is the first report of significant grain proton conduction (∼10 −6 to 10 −7 S cm −1 ) in an iron based perovskite. Water uptake is further shown to be completely reversible, with reformation of BaFeO2.5 when heating the compound to temperatures above ∼450 K under Ar.